Process Modeling of Deagglomeration of Ceramic Nanoparticles in Liquid Metal during Synthesis of Nanocomposites - Payodhar Padhi; Biranchi Narayan Dash; Sachi Kanta Kar (Journal of Nanotechnology)
The cavitation phenomenon is well known to lead to deagglomeration and uniform dispersion of nanoparticles in liquid metal. The nature of flow leading to deagglomeration, the rate of deagglomeration, and the effect of frequency of them has been systematically investigated. It is extremely difficult to experimentally know about them and thus modeling the phenomenon is indispensable. The same has been attempted in the present study. The present study attempts to model the process of deagglomeration and dispersion of ceramic nanoparticles in the vicinity of cavitation using FLUENT 6.2.16. For this a simple representative volume element has been modeled.